Growth, structural change and technological capabilities: Latin America in a comparative perspective - Mario Cimoli; Marcio Holland; Gabriel Porcile; Annalisa Primi; Sebastiàn Vergara (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
Countries differ in terms of technological capabilities and complexity of production structures. According to that, countries may follow different development strategies: one based on extracting rents from abundant endowments, such as labor or natural resources, and the other focused on creating rents through intangibles, basically innovation and knowledge accumulation. The present article studies international convergence and divergence, linking structural change with trade and growth through a North South Ricardian model. The analysis focuses on the asymmetries between Latin America and mature and catching up economies. Empirical evidence supports that a shift in the composition of the production structure in favor of R&D intensive sectors allows achieving higher rates of growth in the long term and increases the capacity to respond to demand changes. A virtuous export-led growth requires laggard countries to reduce the technological gap with respect to more advanced ones. Hence, abundance of factor endowments requires to be matched with technological capabilities development for countries to converge in the long term.
Keywords: O30; O33; 330; Latin America; Structural Change; Technological Capabilities; Growth; Wirtschaftswachstum; Strukturwandel; Internationale Arbeitsteilung; Technischer Fortschritt; Vergleich; Lateinamerika